2020
DOI: 10.1002/mar.21401
|View full text |Cite
|
Sign up to set email alerts
|

All eyes on you: The social audience and hedonic adaptation

Abstract: Marketers have a keen interest in keeping customers happy past the point of product acquisition. However, consumer happiness with products typically declines over time, a process called "hedonic adaptation." Understanding this process is essential for managing consumers' post-acquisition experiences, and yet marketers have not explored how the ubiquitous social environment influences hedonic adaptation. We explore the effect of a social audience (i.e., the presence of others and the perception that those other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…The elevated inclination towards SM also cultivates the fear of missing out (FOMO) among young adults [49], which led them to develop an emotional state of anxiety due to the fear that one is not included in perceived positive events that others were engaged in [50]. Although SM users tend to intentionally attract positive social feedback by filtering or editing their posts [35], [51], the satisfaction of receiving the desired feedback would not last long [52], and they would be falling into another FOMO state, craving for more positive social feedback, especially when people whom they considered significant have not provided them with any desired feedback [53]. This cycle would increase the anxiety to the students who experience it, due to the absence of physical connectivity that convinces them that their peers would always be there for them without them having to check on their SM account [54].…”
Section: Introductionmentioning
confidence: 99%
“…The elevated inclination towards SM also cultivates the fear of missing out (FOMO) among young adults [49], which led them to develop an emotional state of anxiety due to the fear that one is not included in perceived positive events that others were engaged in [50]. Although SM users tend to intentionally attract positive social feedback by filtering or editing their posts [35], [51], the satisfaction of receiving the desired feedback would not last long [52], and they would be falling into another FOMO state, craving for more positive social feedback, especially when people whom they considered significant have not provided them with any desired feedback [53]. This cycle would increase the anxiety to the students who experience it, due to the absence of physical connectivity that convinces them that their peers would always be there for them without them having to check on their SM account [54].…”
Section: Introductionmentioning
confidence: 99%
“…Our work advances the satiation literature, which previously has primarily studied solo experiences, with little attention to social factors in satiation. Some past work has shown that public (vs. private) experience can affect an individual’s ongoing hedonic judgments due to others admiring one’s chosen item (Chugani & Irwin, 2012), or scrutiny of the set of items chosen by one over time (Ratner & Kahn, 2002). In contrast, our theory does not rely on any admiration, scrutiny, or any such judgment that public consumption might encourage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our theory does not rely on any admiration, scrutiny, or any such judgment that public consumption might encourage. We emphasize mutual experience of the same thing with others (i.e., coexperience), rather than the public versus private distinction (Chugani & Irwin, 2012; Ratner & Kahn, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hedonic Adaptation literature most relevant to recommendation systems, studies consumption scenarios. [8]'s experiment lets students choose a sticker and attach it to an everyday object. Eliciting self-reported happiness with the sticker, the study finds a 4.5 point decline on a 100-point scale of reported happiness with a sticker in a 3-day interval.…”
Section: Hedonic Adaptationmentioning
confidence: 99%